Associations Between Effortful Control, Cortisol Awakening Response, and Depressive Problems in Latino Preadolescents. (August 2019) - Taylor, Zoe E.; Evich, Carly D.; Marceau, Kristine; Nair, Nayantara; Jones, Blake L.
The present study examined associations between effortful control, a trait marker of self-regulation, adaptive hypothalamic-pituitary-adrenal (HPA) system functioning (as reflected by the cortisol awakening response [CAR]), and concurrent and longitudinal depressive problems, in a sample of preadolescent Latino youth ( N = 119, mean age = 11.53 years, 59% girls). We hypothesized that trait readiness for self-regulation (specifically effortful control) could be related to physiological state readiness for self-regulation (as measured using the Cortisol Awakening Response or CAR), and that both may counter depressive problems. We found that youth's CAR was positively associated with effortful control, and negatively with youth depressive problems. Effortful control and youth depressive problems were also negatively associated. Longitudinal relations of CAR and effortful control on depressive problems at T2 were not significant in the structural equation model after controlling for T1 depressive problems, although these variables were significant in the bivariate correlations. Results suggest that both trait regulation and physiological regulation may counter depressive problems in Latino youth.